Digital Forensics and Cyber Crime Investigation : Recent Advances and Future Directions - Abd El-Latif, Ahmed A., 1984-; Tawalbeh, Lo'ai; Mohanty, Manoranjan (Editor); Gupta, Brij B., 1982-; Psannis, Konstantinos E. (CRC Press, 2025)
"In the ever-evolving landscape of digital forensics and cyber-crime investigation, staying ahead with the latest advancements is not just advantageous-it's imperative. "Digital Forensics and Cyber Crime Investigation: Recent Advances and Future Directions" serves as a crucial bridge, connecting the dots between the present knowledge base and the fast-paced developments in this dynamic field. Through a collection of meticulous research and expert insights, this book dissects various facets of digital forensics and cyber security, providing readers with a comprehensive look at current trends and future possibilities. Distinguished by its in-depth analysis and forward-looking perspective, this volume sets itself apart as an indispensable resource for those keen on navigating the complexities of securing the digital domain. This book aims to serve as a beacon for practitioners, researchers, and students who are navigating the intricate world of digital forensics and cyber security. By offering a blend of recent advancements and speculative future directions, it not only enriches the reader's understanding of the subject matter but also inspires innovative thinking and applications in the field. Whether you're a seasoned investigator, an academic, or a technology enthusiast, "Digital Forensics and Cyber Crime Investigation: Recent Advances and Future Directions" promises to be a valuable addition to your collection, pushing the boundaries of what's possible in digital forensics and beyond"--